2020
DOI: 10.3390/ijerph17186883
|View full text |Cite
|
Sign up to set email alerts
|

Work–Family Conflict, Emotional Responses, Workplace Deviance, and Well-Being among Construction Professionals: A Sequential Mediation Model

Abstract: Given the dynamic, complex, and highly demanding project environment, construction professionals are particularly likely to experience a high level of work–family conflict. Taking an emotional resource perspective and on the basis of affective events theory, this study tested negative affect and emotional exhaustion as sequential mediators between two directions of work–family conflict and workplace well-being or deviance behavior. The theoretical model was examined using data collected at two time points from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 90 publications
(145 reference statements)
1
20
0
Order By: Relevance
“…Weiss and Cropanzano's ( 50 ) affective events theory explains that employees' internal influences (e.g., emotions) and reactions to the work environment can affect job performance and satisfaction. Research has found evidence that is consistent with this theory ( 49 , 51 , 52 ). For example, NA is predictive of workplace deviance, including absenteeism, theft, and poor job performance, as well as low well-being ( 49 , 51 , 52 ).…”
Section: Literature Reviewmentioning
confidence: 77%
See 4 more Smart Citations
“…Weiss and Cropanzano's ( 50 ) affective events theory explains that employees' internal influences (e.g., emotions) and reactions to the work environment can affect job performance and satisfaction. Research has found evidence that is consistent with this theory ( 49 , 51 , 52 ). For example, NA is predictive of workplace deviance, including absenteeism, theft, and poor job performance, as well as low well-being ( 49 , 51 , 52 ).…”
Section: Literature Reviewmentioning
confidence: 77%
“…Research has found evidence that is consistent with this theory ( 49 , 51 , 52 ). For example, NA is predictive of workplace deviance, including absenteeism, theft, and poor job performance, as well as low well-being ( 49 , 51 , 52 ). Notably, Chen et al ( 49 ) found that PA and NA mediated the relations between work conditions and well-being.…”
Section: Literature Reviewmentioning
confidence: 77%
See 3 more Smart Citations